How an innovative student association can emerge in a context of constraint? The case of Addec, the Cameroon Students' Rights Association - (:unkn) unknown (My University, 2013)
African dynamics in a multipolar World AEGIS-ECAS 2013, 5th European Conference on African Studies http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2327
Keywords: African Research